Formation of Theoretical and Methodological Assumptions in the Assessment of Significance of the Bioeconomy in the Country Economy - Biekša, Kęstutis; Baležentis, Tomas (Problemy Ekorozwoju, 2019)
In order to ensure sustainable development of the modern economies, there is a need for transforming the linear economy model to circular or green economy model. Bioeconomy can contribute to this goal by ensuring the use of bioproducts and biotechnologies. The flow of material and energy in the bioeconomy is based on the use of biomass and renewable sources for food, feed, and materials production. Circulation principle reduces the amount of waste and increases the efficiency of resources use. It is important to discuss the notions of bioeconomy as described in the strategical and legal documents for bioeconomy development. This research mainly focuses on the theoretical and methodological assumptions of bioeconomy, the main measures for stimulating the development of bioeconomy. We also review the trends of the development of bioeconomy across different countries.